Toward a reverse adaptation view in cross-cultural management - Luo, Yadong (Emerald Publishing Limited, 2016)
Purpose – Contrasting local adaptation, which focusses on foreign multinationals learning about and adapting to local (host country) culture and environment, reverse adaptation refers to the case where an MNE’s local employees learn, assimilate and modify their personal behavior (e.g. values, norms) and professional competence (e.g. standards, goals, language, knowledge, capabilities) in order to fit the MNE’s global mindset and global competence set so that they can be internationally reassigned. The purpose of this paper is to take the first step toward addressing this nascent phenomenon and practice. Design/methodology/approach – This study uses combined inductive and ethnographic methods to explore the importance, process and practice of reverse innovation. This study defines reverse adaptation, illustrates the major driving forces underlying reverse adaptation, and suggests how MNEs should prepare for it. As reverse adaptation is a promising area for research, this paper also proposes a research agenda for international management scholars. Findings – MNEs need to act at both local and global levels in a way that recognizes the interdependence between the two. Too often global companies have approached their local talent needs in an uncoordinated and unproductive way. Reverse adaptation view suggests that MNEs can create a competitive advantage by taking a global approach to talent. Cultivating and transforming local talent to become global talent necessitates endeavor from a wide range of corporate, subsidiary and individual levels, in cultural, professional, structural, informational and organizational aspects.Originality/value – Reverse adaptation is a promising area of research because it provides the opportunity to enrich mainstream theories and literatures in a number of areas. This nascent phenomenon has not yet been studied, and this paper represents the first effort to do so. From both academic and practice viewpoints, reverse adaptation has a significant impact on global talent management, knowledge flow across borders, capability catchup and global integration design.Today’s glocalized business world, with heightened integration of world economy, creates an expectation for the continuing growth of reverse adaptation.